PENGARUH KEMAJUAN TEKNOLOGI, PENGETAHUAN INVESTASI, DAN LITERASI KEUANGAN SYARIAH TERHADAP MINAT INVESTASI PADA CRYPTOCURRENCY: STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS KAHURIPAN KEDIRI - Wulansari, Lastri; Rahmad, Rahmad (Jurnal Gici Jurnal Keuangan dan Bisnis, 2025)
The rapid advancement of digital technology has significantly reshaped investment behavior, particularly among the younger generation,who show increasing interest in Cryptocurrency. This study aims to examine th einfluence of technological advancement, investment knowledge, and Islamic financial literacy on students’ interest in investing in Cryptocurrency. The research was conducted on students from the Faculty of Economics and Business at Universitas Kahuripan Kediri, cohorts 2022–2024. Using a quantitative approach, data were collected through questionnaires and analyzed with multiple linear regression via SPSS version 25. The findings indicate that technological advancement and investment knowledge have a positive and significant effect on Cryptocurrency investment interest. Conversely, Islamic financial literacy does not show a significant effect. These results suggest that access to technology and solid investment understanding are crucial in shaping youth investment preferences. This research provides insights for enhancing digital financial literacy in higher education and developing investment strategies aligned with Islamic values.